2009
DOI: 10.1007/s12094-009-0375-1
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis as a diagnostic pitfall of pancreatic cancer

Abstract: Sarcoidosis (SA) is accompanied by malignancy more than can be explained by chance. Cancer can occur in patients with an established diagnosis of SA and SA can subsequently develop in a cancer patient. Malignancy can also be associated with the occurrence of sarcoid reactions (SR), which are typically restricted to the regional lymph nodes. Problems may also arise in distinguishing between tumour-related SRs and true systemic SA. Here we present a case with both SA and pancreatic cancer, and we discuss the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…However, cases of ("atypical sarcoid-like reaction") in distant lymph nodes have been observed [3]. Other studies such as Mastroroberto et al reported the first case of association of sarcoidosis and pancreatic neuroendocrine tumor [3] and Zambrana et al also reported a case with both sarcoidosis and pancreatic cancer [7]. In this study, we report, to our knowledge, the first case of sarcoidosis associated with pseudopapillary pancreatic tumor.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, cases of ("atypical sarcoid-like reaction") in distant lymph nodes have been observed [3]. Other studies such as Mastroroberto et al reported the first case of association of sarcoidosis and pancreatic neuroendocrine tumor [3] and Zambrana et al also reported a case with both sarcoidosis and pancreatic cancer [7]. In this study, we report, to our knowledge, the first case of sarcoidosis associated with pseudopapillary pancreatic tumor.…”
Section: Discussionmentioning
confidence: 55%
“…Malignancy can also be associated with the occurrence of sarcoid reactions. Problems may also arise in distinguishing between tumorrelated sarcoid reactions and true systemic sarcoidosis [7]. So, in this study revision of pathological specimen was then carried out in order to make a differential diagnosis between pancreatic tumor associated with sarcoidosis, or the presence of a pancreatic granuloma as a part of a systemic sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, many patients with solid tumors develop "sarcoid-like reactions", which commonly involve regional lymph nodes and sometimes the skin [7]. To date, very few cases exist in the literature on the occurrence of pancreatic cancer in patients with sarcoidosis [8].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcoidosis is accompanied by malignancy more often than can be explained by chance. 8 Computed tomographic findings are not specific for the diagnosis of pancreatic sarcoidosis. An ill-defined pancreatic head mass, narrowing the common bile duct with or without pancreatic duct dilatation and enlarged lymph nodes are the common computed tomographic findings.…”
Section: Discussionmentioning
confidence: 99%